Efficacy and safety of setmelanotide, an MC4R agonist, in individuals with severe obesity due to LEPR or POMC deficiency: single-arm, open-label, multicentre, phase 3 trials. Issue 12 (December 2020) - Clément, Karine; van den Akker, Erica; Argente, Jesús; Bahm, Allison; Chung, Wendy K; Connors, Hillori; De Waele, Kathleen; Farooqi, I Sadaf; Gonneau-Lejeune, Julie; Gordon, Gregory; Kohlsdorf, Katja; Poitou, Christine; et al.
Summary: Background: The melanocortin 4 receptor (MC4R), a component of the leptin–melanocortin pathway, plays a part in bodyweight regulation. Severe early-onset obesity can be caused by biallelic variants in genes that affect the MC4R pathway. We report the results from trials of the MC4R agonist setmelanotide in individuals with severe obesity due to either pro-opiomelanocortin (POMC) deficiency obesity or leptin receptor (LEPR) deficiency obesity. Methods: These single-arm, open-label, multicentre, phase 3 trials were done in ten hospitals across Canada, the USA, Belgium, France, Germany, the Netherlands, and the UK. Participants aged 6 years or older with POMC or LEPR deficiency obesity received open-label setmelanotide for 12 weeks. Participants with at least 5 kg weight loss (or ≥5% if weighing <100 kg at baseline) entered an 8-week placebo-controlled withdrawal sequence (including 4 weeks each of blinded setmelanotide and placebo treatment) followed by 32 additional weeks of open-label treatment. The primary endpoint, which was assessed in participants who received at least one dose of study medication and had a baseline assessment (full analysis set), was the proportion of participants with at least 10% weight loss compared with baseline at approximately 1 year. A key secondary endpoint was mean percentage change in the most hunger score of the 11-point Likert-type scale at approximately 1 year on the therapeutic dose, which was assessed in a subset of participants aged 12 years or older in the full analysis set who demonstrated at least 5 kg weight loss (or ≥5% in paediatric participants if baseline bodyweight was <100 kg) over the 12-week open-label treatment phase and subsequently proceeded into the placebo-controlled withdrawal sequence, regardless of later disposition. These studies are registered with ClinicalTrials.gov, NCT02896192 and NCT03287960 . Findings: Between Feb 14, 2017, and Sept 7, 2018, ten participants were enrolled in the POMC trial and 11 participants were enrolled in the LEPR trial, and included in the full analysis and safety sets. Eight (80%) participants in the POMC trial and five (45%) participants in the LEPR trial achieved at least 10% weight loss at approximately 1 year. The mean percentage change in the most hunger score was −27·1% (n=7; 90% CI −40·6 to −15·0; p=0·0005) in the POMC trial and −43·7% (n=7; −54·8 to −29·1; p<0·0001) in the LEPR trial. The most common adverse events were injection site reaction and hyperpigmentation, which were reported in all ten participants in the POMC trial; nausea was reported in five participants and vomiting in three participants. In the LEPR trial, the most commonly reported treatment-related adverse events were injection site reaction in all 11 participants, skin disorders in five participants, and nausea in four participants. No serious treatment-related adverse events occurred in both trials. Interpretation: Our results support setmelanotide for the treatment of obesity and hyperphagia caused by POMC or LEPR deficiency. Funding: Rhythm Pharmaceuticals.